Effect of Staining and Bleaching on Color Change of Resin Composite Restorative Materials - Z. Osman, Eman; M. Betamar, Naeima; H. Bubteina, Nagat; A. Mohamed, Rafa (Libyan Journal of Dentistry, 2022)
Aims: To evaluate the color change of three resin composites (nanohybrid; Filtek Z250XT, microhybrid, DenFil, and nanoceram; Zenit) after exposure to tea, coffee, artificial saliva, and bleaching procedure. Materials and Methods: A total of 162 disc-shaped specimens (12.2mm diameter, and 2.2mm thickness) from the three resin composites were prepared in a silicon mold, then divided into 3 groups according to the type of resin composite. Each group was subdivided into three experimental groups (n=18), and immersed into staining solutions; tea, coffee, and artificial saliva for 3h/day over 28 days. A bleaching agent (Opalescence 20 home bleach) was applied to previously stained specimens for 3h/day over 14 days. The color measurement for each specimen was performed according to CIE L*a*b* system using a spectrophotometer on three occasions: i) at baseline, ii) after staining, and iii) after bleaching. The color differences delta E (ΔE) between the three measurements were calculated and the obtained data was statistically analyzed. Results: The three composites showed significant color change after immersion in tea, and coffee solutions (P˂0.05), and after the bleaching (P˂0.05). DenFil showed the most color change followed by Z250XT. Zenit was the least affected by staining solutions. Tea solution caused more color change than the coffee solution. Artificial saliva showed insignificant color change for all groups (P=0.07). Conclusions: Exposure to drinks with staining ability such as tea and coffee can significantly affect the color stability of the tested composites. The bleaching agent was effective in removing the stains and restoring the color of all composites near or at baseline color.